KURIKULUM MERDEKA DAN TELAAH PERAN KONSELOR DI SEKOLAH - Hanik Mufaridah; Dian Mego Anggraini; Ahmad Andry Budianto (Maddah : Jurnal Komunikasi dan Konseling Islam, 2023)
This study employs a qualitative research approach with a type of literature study research in which the examines various types of literature, including scientific articles and books available both online and offline, with the goal of examining independent curricula and the role of school counselors. The findings of this study can only be explained if the independent curriculum created by the ministry of education aims to maximize students’ potential in the areas of reading, numeracy, and character development. This study’s conclusion is that all stakeholders must support and actively work for the success of the curriculum, such as by providing suitable online and offline learning and employment opportunities. infrastructure and facilities to ensure that its use and implementation in the field go smoothly.